2020
DOI: 10.3390/jcm9072211
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality-Assisted Periosteum Pedicled Flap Harvesting for Head and Neck Reconstruction: An Anatomical and Clinical Viability Study of a Galeo-Pericranial Flap

Abstract: Head and neck reconstructive surgeons have recently explored new perspectives in bone restoration using periosteum carrier flaps. Following this idea, we explored the possibility of harvesting a galeo-pericranial flap. The present work studies the vascular supply of the pericranial temporo-parietal region in order to assess the possibility of harvesting a galeo-pericranial flap based on the superficial temporalis vascularization. Anatomical dissections were performed at the Anatomical Institute of the Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The VOSTARS device can have prospective use also in tumor and head and neck reconstructive surgery, e.g., in providing anatomical visualization and in supporting mandibular complex reconstruction. Some previous studies reported experiences of AR-assisted navigation used in combination with CAD/CAM technology to guide the positioning of the fibular osteotomy cutting guide [7], as well as to facilitate anatomical visualization during free flap harvesting [42], but in both cases, the AR guidance was performed using hand-held mobile devices (smartphone or tablet). VOSTARS can represent an improved AR-assisted navigation system that allows the surgeon to view directly in front of his eyes the virtual content superimposed on the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The VOSTARS device can have prospective use also in tumor and head and neck reconstructive surgery, e.g., in providing anatomical visualization and in supporting mandibular complex reconstruction. Some previous studies reported experiences of AR-assisted navigation used in combination with CAD/CAM technology to guide the positioning of the fibular osteotomy cutting guide [7], as well as to facilitate anatomical visualization during free flap harvesting [42], but in both cases, the AR guidance was performed using hand-held mobile devices (smartphone or tablet). VOSTARS can represent an improved AR-assisted navigation system that allows the surgeon to view directly in front of his eyes the virtual content superimposed on the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the factors that influence the periosteal inherent regenerative capacity is mandatory for a predictable application in reconstructive approaches. The pericranium is a clinically relevant source due to the feasibility for harvesting larger periosteal tissues (Battaglia et al 2020). In this study, the ectopic employment of periosteal grafts and flaps in muscle IVBs was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike VR, which creates a totally artificial environment, AR uses the existing real environment and overlays new information on top of it, thus providing a composite view. In recent years, AR has been proposed and applied as an aiding tool in many healthcare sectors, including neurosurgery [13], urology [14][15][16], orthopedics [17,18], and craniomaxillofacial surgery [19][20][21][22][23]. AR is rapidly growing with many new potential applications also in the medical education field [24].…”
Section: Introductionmentioning
confidence: 99%